Strategi Guru dalam Membiasakan Kebersihan Lingkungan sebagai Pendidikan Akhlak di Madrasah Ibtidaiyah - Oktio Frenki Biantoro; Muhammad Istiqlal (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
Moral education in Madrasah Ibtidaiyah plays an important role in shaping student character. However, its implementation still faces challenges, so it is necessary to study the concrete strategies teachers use to instill these values contextually and applicatively. This research uses a qualitative approach with a case study method. Data collection techniques were conducted through participant observation, in-depth interviews, and document analysis. Data were analyzed using interactive analysis techniques that included data condensation, data presentation, and verification by maintaining data validity through credibility, transferability, dependability, and confirmability. The results showed that moral education in environmental hygiene is realized through habituation, exemplary, and punishment strategies. These strategies are applied in routine activities such as class pickets, environmental clean-up actions, and daily clean-living practices. These efforts shape the character of students who are responsible, disciplined, and care about the environment, as well as creating a clean, healthy learning atmosphere and supporting improving learning quality. The conclusions and contributions of this study indicate that moral education strategies through habituation, exemplification, and punishment effectively shape students' characters who care about the environment and contribute to creating a clean, healthy school culture and supporting quality teaching and learning processes.